Effect of the C-terminal proline repeats on ordered packing of squid rhodopsin and its mobility in membranes. - Venien-Bryan, C; Davies, A; Langmack, K; Baverstock, J; Watts, A; Marsh, D; Saibil, H (1995)
Negative stain electron microscopy and saturation transfer electron spin resonance spectroscopy have been used to compare the lattice ordering and in-plane membrane mobility of full-length and C-terminally cleaved squid rhodopsin. The C-terminus of squid rhodopsin contains a negatively charged region followed by 9-10 repeats of a proline-rich sequence, not found in rhodopsins other than those of cephalopod invertebrates, but similar proline repeats are found in other, unrelated membrane proteins. We find that the proline repeats cluster the rhodopsins into small groups, interfering with two-dimensional crystallization and maintaining their mobility in the membrane.